C 7 Moriche Palms on Aripe [sic] Savannah, Trinidad - (:unkn) unknown (My University, 2010)
Description on the back of the postcard: "On the open Savannahs and in the vicinity of the Pitch Lake the Moriche Palm (Mauritia seligera) occurs in great abundance, usually in groups forming a prominent feature of the landscape."
Colour: Sepia; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Moriche Palm--Trinidad and Tobago; Mauritia flexuosa--Trinidad and Tobago; Pitch Lake, The; Savannas--Trinidad and Tobago